Well completion practices - Md. Yassin, Abu Azam; Mohd. Arshad, Azmi; Ismail, Issham (UTM Publisher, 1997)
This book was translated from English to Malay. It is an early section of Chapter 1 (Well completion practices). Other chapters covered are Wellhead and ubing accessories, Perforation, and Sand control.